2008
DOI: 10.1093/jxb/ern263
|View full text |Cite
|
Sign up to set email alerts
|

Modules of co-regulated metabolites in turmeric (Curcuma longa) rhizome suggest the existence of biosynthetic modules in plant specialized metabolism

Abstract: Turmeric is an excellent example of a plant that produces large numbers of metabolites from diverse metabolic pathways or networks. It is hypothesized that these metabolic pathways or networks contain biosynthetic modules, which lead to the formation of metabolite modules—groups of metabolites whose production is co-regulated and biosynthetically linked. To test whether such co-regulated metabolite modules do exist in this plant, metabolic profiling analysis was performed on turmeric rhizome samples that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…3; Supplemental Figs. S1 and S2; Supplemental Table S2; Xie et al, 2009). The normalized data used to produce Figure 3 revealed that the known metabolites observed in Solanum trichomes are differentially distributed between trichome types and species and that this variation is generally more evident between species than within.…”
Section: Gross Comparisons Of Trichome Metabolite Profiles In Solanummentioning
confidence: 99%
“…3; Supplemental Figs. S1 and S2; Supplemental Table S2; Xie et al, 2009). The normalized data used to produce Figure 3 revealed that the known metabolites observed in Solanum trichomes are differentially distributed between trichome types and species and that this variation is generally more evident between species than within.…”
Section: Gross Comparisons Of Trichome Metabolite Profiles In Solanummentioning
confidence: 99%
“…The biosynthetic pathway of these diarylheptanoids has not yet been elucidated and several routes have been hypothesized. Xie et al (104), after using metabolic profiling analysis, proposed that the biosynthetic pathway belongs to a different metabolite module (Fig. 2) and that they are not intermediates in curcuminoid biosynthesis that belong to another biosynthetic module (Fig.…”
Section: Curcuminoid Production In Curcuma Longamentioning
confidence: 99%
“…1), which cannot use caffeoyl-CoA as a substrate and produce the major curcuminoids. Furthermore, Xie et al (104) reported that some PKS, instead of using caffeoyl-CoA, use 5-hydroxy-feruloyl-CoA or feruloyl-CoA and coumaroylCoA to produce 5=-hydroxy-curcumin and 5=-hydroxy-demethoxycurcumin, respectively. Dihydrocurcuminoids, which are dihydro derivatives of curcuminoids (103), have also been identified in C. longa, for example, di- hydrodemethoxycurcumin, dihydrobisdemethoxycurcumin, and dihydrocurcumin.…”
Section: Curcuminoid Production In Curcuma Longamentioning
confidence: 99%
“…An exciting and promising approach to understand these mechanisms is described in the paper by Xie et al (2009). The authors have coupled state of the art metabolomic analyses with novel bioinformatic techniques to identify apparent 'metabolic modules' in turmeric (Curcuma longa) rhizomes.…”
mentioning
confidence: 99%
“…Sixteen different growth and development treatments were performed and metabolically profiled, followed by hierarchical cluster analysis in order to detect co-regulated volatile and non-volatile metabolites. Biosynthetic relationship predictions were then made using the metabolite modules that resulted from the processing of the metabolomic information collected (Xie et al, 2009). The dissection of the metabolic information into metabolic modules led to the conclusion that more than one polyketide synthase is involved in diarylheptanoid biosynthesis in turmeric rhizomes, but the potential for using a similar approach in deciphering complex and apparently unrelated metabolic pathways is also very promising.…”
mentioning
confidence: 99%